2021
DOI: 10.4094/chnr.2021.27.2.137
|View full text |Cite
|
Sign up to set email alerts
|

An electronic medical record-based fall risk assessment tool for pediatric inpatients in South Korea: Improved sensitivity and specificity

Abstract: Purpose: To develop a fall risk assessment tool to predict fall risk in pediatric inpatients.Methods: Three tools widely used in clinical practice (Humpty Dumpty Fall Scale, General Risk Assessment for Pediatric Inpatient Falls, and Seoul National University Hospital Pediatric Fall Risk Scale) were examined, and assessment items were extracted. Employing a case-control design, 29 children who experienced falls during hospital stays were selected as the "fall" group, and a control group (93 children) was select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
0
5
0
6
Order By: Relevance
“…(25) Na avaliação das propriedades de medida, os coeficientes de confiabilidade foram semelhantes a de outros estudos que avaliaram a escala (Kappa>0,80). (6,8,14) A avaliação da validade demonstra se o instrumento realmente mensura o risco de queda entre crianças e adolescentes. Para isso, os escores da versão brasileira da HDFS foram correlacionados com os domínios do Instrumento de Classificação de Pacientes Pediátricos e apresentaram correlações significantes com os domínios Paciente e Procedimentos terapêuticos -confirmando as hipóteses estabelecidas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…(25) Na avaliação das propriedades de medida, os coeficientes de confiabilidade foram semelhantes a de outros estudos que avaliaram a escala (Kappa>0,80). (6,8,14) A avaliação da validade demonstra se o instrumento realmente mensura o risco de queda entre crianças e adolescentes. Para isso, os escores da versão brasileira da HDFS foram correlacionados com os domínios do Instrumento de Classificação de Pacientes Pediátricos e apresentaram correlações significantes com os domínios Paciente e Procedimentos terapêuticos -confirmando as hipóteses estabelecidas.…”
Section: Discussionunclassified
“…A HDFS foi desenvolvida com o objetivo de classificar crianças e adolescentes de acordo com o risco para queda, no ambiente hospitalar e ambulatorial, e tem demonstrado adequada confiabilidade interobservadores (Kappa>0,80) e sensibilidade acima de 70%; entretanto, com baixa especificidade (<40%). (6,7,(8)(9)(10)(11)(12)(13)(14)(15)(16) Considerando que não foram identificados, no Brasil, instrumentos específicos e validados para avaliar o risco de quedas em crianças e adolescentes, o contexto da segurança do paciente e a necessidade de avaliar o risco de quedas para implementação and significant correlations were found between The Humpty Dumpty Scale and the Patient (r=0.5184; p<0.0001) and Therapeutic Procedures (r=0.2143; p<0.0332) domains of the patient classification instrument. With the Family domain (r=0.0676; p=0.5060), no significant relationships were achieved.…”
Section: Introductionunclassified
“…The authors concluded that the more specific an assessment tool, the greater its accuracy in predicting falls. 11 Evidence was also gained from one level III source and one level IV source. The level III source was a quality improvement project that sought to decrease harm resulting from pediatric falls by implementing a fall bundle with elements such as ensuring a safe environment for patients, communicating about fall risk patients with staff, and implementing tools to mitigate fall occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The fifth study, a retrospective case-control study, focused on developing a new fall risk assessment tool by evaluating three commonly used fall risk tools. The authors concluded that the more specific an assessment tool, the greater its accuracy in predicting falls 11 …”
Section: Introductionmentioning
confidence: 99%
“…Falls are the most common type of adverse events reported for hospitalized children (Alemdaroglu et al, 2017 ; Fujita et al, 2013 ; Lee et al, 2013 ), which can cause serious harm to paediatric patients (AlSowailmi et al, 2018 ; Feuerlicht et al, 2020 ; Kim & Lee, 2021 ), and increase the length of stay (Almis et al, 2017 ). As a result, falls of inpatient children are an important issue as part of initiatives to prevent inpatient safety accidents (Kim, Lim, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%